Perlindungan Hukum Konsumen dari Praktik Iklan yang Menyesatkan oleh Pelaku Usaha di Kota Kupang Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Dio Afriyanto Minta; Agustinus Hedewata; Sukardan Aloysius (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to (1) find out the role of business actors in making misleading promotions according to Law Number 8 of 1999 concerning Consumer Protection, and (2) to find out the legal protection for consumers in Kupang City against misleading information provided by business actors through product promotion based on Law Number 8 of 1999 concerning Consumer Protection. This study uses an empirical judiciary method using primary data and secondary data. The results of the study show that (1) The role of business actors in making misleading advertising promotions is depicted in practices such as false advertising, deceptive practices, and fraudulent advertising. Business actors have a role in creating advertisements that do not match reality, providing incorrect information, and manipulating consumers to make purchase decisions without correct information. The impact includes harming consumers, damaging market integrity, and potentially harming the overall business image. Mistakes in this kind of marketing practice not only violate consumer protection laws, but can also shake consumer trust and affect market fairness and integrity, and (2) In the face of misleading information from business actors through product promotion in Kupang City, legal protection for consumers is essential, especially with reference to Law Number 8 of 1999 concerning Consumer Protection. This law provides a legal basis to protect consumers from dishonest and harmful advertising practices. By emphasizing principles such as benefits, fairness, balance, security, consumer safety, and legal certainty, the Act creates a foundation for consumer protection.